Play the City. Geografia della “città amatoriale”: teorie, applicazioni, prospettive - Paolo Simoni; Ilaria Ferretti; Nicola M. Dusi (Cinergie, 2017)
Our article is divided into three connected sections. The first one discusses the image of the city in amateur movies, taking into account the cinematic urban archeology of home movies and operational practices of databases, Geographical Information Systems, maps, installations. We propose the notion of “amateur city” as the synthesis of multiple, located views collected in a long period of time projected onto a map. The second section describes the Play the City app, a digital tool to map and navigate the urban space, between the past and the present, through 120 clips of amateur filmmakers. The third part deals with the idea of mapping the “storyworld” of a city through the app and opens up some theoretical perspectives on film images and geo-located systems.